Is weakness of will possible in Plato’s Laws? Platonic drifts regarding a Socratic problem - Bieda, Esteban (Revista de Filosofía, 2018)
Platonic philosophy is deeply marked by an epistemological concern. In this context Plato adopts the so called “Socratic Intellectualism”, which implies a strong rejection of the possibility of incontinent actions, weakness of will or akrasía. In this paper I will try to show that Plato himself undertook a revision of that Socratic theory in the Laws, above all because of a profound change in his conception regarding human nature.